The role of microRNAs in chronic pseudomonas lung infection in Cystic fibrosis. (May 2019) - Fesen, Katherine; Silveyra, Patricia; Fuentes, Nathalie; Nicoleau, Marvin; Rivera, Lidys; Kitch, Diane; Graff, Gavin R.; Siddaiah, Roopa
Abstract: Background: Cystic Fibrosis (CF) is the most common life limiting genetic disorder, characterized by chronic respiratory failure secondary to inflammation and chronic bacterial lung infection. Pseudomonas aeruginosa lung infection is associated with more severe lung disease and rapid progression of respiratory failure when compared to Staphylococcus aureus infection. We hypothesized that a specific signature of epigenetic factors targeting specific gene transcripts contributes to the increased morbidity seen in CF patients with chronic Pseudomonas infection. Methods: We collected exhaled breath condensate (EBC) from 27 subjects and evaluated miRNA signatures in these samples using commercial PCR array. We identified predicted mRNA targets and associated signaling pathways using Ingenuity Pathway Analysis. Results: We found 11 differentially expressed miRNAs in EBC of patients infected with Pseudomonas aeruginosa compared to EBC from CF patients who were not chronically infected with Pseudomonas aeruginosa (p < 0.05). Six of these miRNAs (hsa-miRNA-1247, hsa-miRNA-1276, hsa-miRNA-449c, hsa-miRNA-3170, hsa-miRNA-432-5p and hsa-miR-548) were significantly different in the CF Pseudomonas positive group when compared to both the CF Pseudomonas negative group and healthy control group. Ingenuity pathway analysis (IPA) revealed organismal injury and abnormalities, reproductive system disease and cancer as the top diseases and bio functions associated with these miRNAs. IPA also detected RELA, JUN, TNF, IL-10, CTNNB1, IL-13, SERPINB8, CALM1, STARD3NL, SFI1, CD55, RPS6KA4, TTC36 and HIST1H3D as the top target genes for these miRNAs. Conclusion: Our study identified 6 miRNAs as epigenetic factors specifically associated with chronic Pseudomonas infection in patients with CF. Highlights: Specific miRNAs are over/under expressed in chronic pseudomonas infection in patients with Cystic fibrosis in EBC samples. The top miRNAs overexpressed are miRNA-1247, miRNA-1276, miRNA-449c, miRNA-3170, miRNA-432-5p and miRNA-548. Ingenuity pathway analysis reveals interactions between RELA, JUN, TNF, IL-10, IL-13, SERPINB8, CD55, RPS6KA4, TTC36. These miRNAs associated pathways involved cell proliferation and tumor cell apoptosis along with Wnt/b-catenin signaling.